Antifungal activity of Rhopalurus crassicauda venom against Candida spp. (June 2022) - Zottich, Umberto; de Oliveira, Isadora Sousa; Fereira, Isabela Gobbo; Cerni, Felipe Augusto; Karla de Castro Figueiredo, Bordon; Arantes, Eliane Candiani; Gomes, Valdirene Moreira; Dias, Germana Bueno; Pucca, Manuela Berto
Abstract: Fungal infections are becoming a serious problem of human diseases, being one of the most important fungal pathogens the yeast of the genus Candida . So far, fungal infection treatment faces different challenges, including the limited number of therapeutic drugs. Scorpions are known to be a valuable source of biologically active molecules, especially of peptide-derived molecules with a variety of biological effects and useful, lead compounds for drugs development. Here, we pioneer described the antifungal effect of venom, mucus, and the major toxin (Rc1) from Rhopalurus crassicauda scorpion. These results support the potential for Rc1 to be further investigated as a novel antifungal therapeutic to treat Candida infections. Graphical abstract: Image 1 Highlights: Fungal infection treatment presents limited number of therapeutic drugs. R. crassicauda venom and major toxin inhibit Candida spp. grown in vitro . R. crassicauda venom-derived toxins may be a rich source of antifungal compounds.